The long-term survival outcomes of gastric cancer patients with total intravenous anesthesia or inhalation anesthesia: a single-center retrospective cohort study - Wei-Wei Wu (BMC, 2021)
Abstract Background The relationship between the type of anesthesia and the survival outcomes of gastric cancer patients is uncertain. This study compared the overall outcome of gastric cancer patients after surgery with total intravenous anesthesia (TIVA) or inhalation anesthesia (IHA). Methods Clinicopathological variables of gastric cancer patients were retrieved from the database of the Surgical Gastric Cancer Patient Registry in West China Hospital, Sichuan University. Patients were grouped according to whether they received TIVA or IHA during the operation. Propensity score (PS) matching was used to balance the baseline variables, and survival outcomes were compared between these two groups. In addition, studies comparing survival outcomes between TIVA and IHA used for gastric cancer surgery and published before April 20th, 2020, were identified, and their data were pooled. Results A total of 2827 patients who underwent surgical treatment from Jan 2009 to Dec 2016 were included. There were 323 patients in the TIVA group and 645 patients in the IHA group, with 1:2 PS matching. There was no significant difference in overall survival outcomes between the TIVA and IHA groups before matching the cohort (p = 0.566) or after matching the cohort (p = 0.679) by log-rank tests. In the Cox hazard regression model, there was no significant difference between the TIVA and IHA groups before (HR: 1.054, 95% CI: 0.881–1.262, p = 0.566) or after (HR: 0.957, 95% CI: 0.779–1.177, p = 0.679) PS matching. The meta-analysis of survival outcomes between the TIVA and IHA groups found critical statistical value in the before PS matching cohort (HR 0.74, 95% CI: 0.57–0.96 p < 0.01) and after PS matching cohort (HR: 0.65, 95% CI: 0.46–0.94, p < 0.01). Conclusions Combined with the results of previous studies, total intravenous anesthesia has been shown to be superior to inhalation anesthesia in terms of overall survival for gastric cancer patients undergoing surgical treatment. The selection of intravenous or inhalation anesthesia for gastric cancer surgery should take into account the long-term prognosis of the patient.